The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s13238-013-3911-2
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation and transcriptional analyses of human ESC-derived cardiomyocytes

Abstract: With defined culture protocol, human embryonic stem cells (hESCs) are able to generate cardiomyocytes in vitro, therefore providing a great model for human heart development, and holding great potential for cardiac disease therapies. In this study, we successfully generated a highly pure population of human cardiomyocytes (hCMs) (>95% cTnT + ) from hESC line, which enabled us to identify and characterize an hCM-specific signature, at both the gene expression and DNA methylation levels. Gene functional associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In contrast, our results indicate that amniocyte DNA methylation and gene expression only weakly correlate, and when common functional groups or pathways are analyzed separately, the relationships can be positive, negative or uncorrelated, implying diverse mechanisms regulate different types of genes. In line with our bioinformatics analyses, one previous study documented markedly different DNA methylation patterns for cardiac structural genes compared with cardiac-specific transcription factors (Gu et al, 2014). We propose that these two cardiomyocyte-specific gene categories (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, our results indicate that amniocyte DNA methylation and gene expression only weakly correlate, and when common functional groups or pathways are analyzed separately, the relationships can be positive, negative or uncorrelated, implying diverse mechanisms regulate different types of genes. In line with our bioinformatics analyses, one previous study documented markedly different DNA methylation patterns for cardiac structural genes compared with cardiac-specific transcription factors (Gu et al, 2014). We propose that these two cardiomyocyte-specific gene categories (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…CM differentiation from pluripotent cell sources has already significantly improved our understanding of transcriptional and epigenetic programs involved in human cardiomyogenesis (Bar-Nur et al, 2011;Kattman et al, 2011;Rajala et al, 2011;Paige et al, 2012;Xu et al, 2012;Zwi-Dantsis and Gepstein, 2012;Chow et al, 2013a;Lian et al, 2013;Gu et al, 2014). Extensions of findings from transcriptional studies have resulted in major improvements in CM yield by recapitulation/enhancement of normal differentiation programs (Kattman et al, 2011;Rai et al, 2012;Lian et al, 2013), but what role do epigenetic and epigenomic studies play?…”
Section: Generation and Enrichment Of Pluripotent-cmsmentioning
confidence: 99%
“…Additional studies on bivalent histone marks through CM differentiation have shown that CMs electrophysiology is epigenetically regulated through H3K27me3 and H3K4me3 dynamics and that derived CMs may be primed epigenetically for further maturation (Chow et al, 2013b). Pair-wise promoter DNA methylation studies on hESCs and CMs have shown that DNA hypomethylation also occurs at structural genes during cardiomyogenesis (Gu et al, 2014). In our laboratory, recent work has confirmed CM structural gene promoter hypomethylation, which appears to be progressive over multiple stages of differentiation (manuscript in preparation).…”
Section: Epigenetics Of Pluripotent-cm Differentiationmentioning
confidence: 99%
“…During the early stage of embryonic development, CpG islands maintain unmethylated states in which the majority of genes undergo active demethylation, and obtain DNA methylation patterns specific to certain tissue types and developmental stages [19]. Some studies have detected increases in DNA methylation-mediated epigenetic repression during cardiomyocyte lineage specification or decreases during neurogenesis from ESCs [20,21]. However, in our study, hypomethylation events occurred more often than hypermethylation events upon erythroid differentiation from hESCs, which is in agreement with events during mouse erythropoiesis and the results of study investigating CD34…”
Section: Discussionmentioning
confidence: 99%